Association of Cardiorespiratory Fitness with Vascular Intima- Media Thickness, Elasticity and Fatty Liver in Young Adults : Prospective Special Turku Coronary Risk Factor Intervention Project (STRIP) - Raekumpu, Roope (My University, 2026)
The development of cardiovascular diseases and metabolic-associated fatty liver disease (MASLD) originates in youth. This study aimed to investigate the cross-sectional and longitudinal associations of cardiorespiratory fitness with aortic and carotid intima- media thickness (IMT), arterial elasticity, and the occurrence of fatty liver in young adults at the age of 26 years. Additionally, the sustained effect of a 20-year infancy- onset lifestyle intervention (STRIP cohort) on fitness and common metabolic risk factors were evaluated. This study is a part of the prospective STRIP cohort. Maximal oxygen uptake (VO2max) was measured using a cycle ergometer at the ages of 17 and 26 years. Aortic and carotid IMT, arterial elasticity, and hepatic steatosis were assessed via ultrasonography at the ages of 17 and 26 years. Statistical models were adjusted primarily for sex. Further adjustments were made for the STRIP study group and several cardiometabolic and socioeconomic risk factors. Belonging to the STRIP intervention group was associated with higher cardiorespiratory fitness at the age of 26 years. Fitness at the age of 26 years was directly associated with a thickening of carotid IMT during the 9-year time-period from the age of 17 to 26 years, which remained significant after full adjustments for cardiometabolic risk factors. Longitudinal change in fitness from the age of 17 to 26 years was associated with longitudinal changes in aortic IMT and elasticity, but these associations were attenuated after full adjustment for cardiometabolic risk factors. Low fitness at the ages of 17 and 26 years strongly predicted the occurrence of fatty liver at age 26, with the vast majority of cases clustering in the lowest fitness tertile. Higher fitness at the age of 17 years independently and significantly predicted a lower risk of fatty liver at the age of 26 years (OR [0.824], 95% CI [0.717] – [0.948], after adjusting for sex, STRIP intervention/control group and BMI. The cross-sectional association at the age of 26 years followed a similar trend but reached a borderline significance after full adjustment for sex, STRIP intervention/control group and BMI (OR [0.855], 95% CI [0.731] – [1.000]). Cardiorespiratory fitness is a robust, independent protective factor against fatty liver during the transition to young adulthood. The favorable associations between fitness and vascular structure previously observed in this cohort at the age of 17 years did not persist independently into young adulthood. The observed carotid thickening in fit young adults, unaccompanied by decreased elasticity, suggests physiological vascular remodeling referred to as the 'athlete's artery', rather than pathological aging. Furthermore, long-term, early-life lifestyle counseling provides latent benefits for cardiorespiratory health in young adulthood.
Keywords: cardiorespiratory fitness; fatty liver; arterial elasticity; intima-media thickness; young adults